All Days 2017
DOI: 10.7122/486365-ms
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide in Situ Generation for Enhanced Oil Recovery

Abstract: Carbon dioxide flooding of oil fields around the world is proven as a successfully adopted practice in increasing oil production particularly in marginal wells with low production rates. However, the limitations of this technology lie in the limited supply of carbon dioxide, high capital cost, and infrastructure corrosion. In this work, we present an alternative CO2 flooding method which generates CO2 inside the reservoir to increase oil recovery. The process involves the injection of a concentrated CO2 produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Self‐generated gas technology can effectively solve the storage and transportation problems of gas sources in offshore platform operation. Some early studies have proved its feasibility as a chemical flooding technique for enhanced oil recovery . For example, Wang used urea and ammonium carbamate as reaction agents for the in situ CO 2 technology.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Self‐generated gas technology can effectively solve the storage and transportation problems of gas sources in offshore platform operation. Some early studies have proved its feasibility as a chemical flooding technique for enhanced oil recovery . For example, Wang used urea and ammonium carbamate as reaction agents for the in situ CO 2 technology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang used urea and ammonium carbamate as reaction agents for the in situ CO 2 technology. They found that the in situ CO 2 technology was close to the complex combination flooding technology such as surfactant recovery and alkali flooding in terms of tertiary oil recovery . In addition, the effects of injection method, agent concentration, and high divalent ion level on the reaction kinetics and recovery performance of the urea system were also investigated .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even with current stimulation and completion technologies, many fields are expected to produce less than 10% of initial oil in place. CO 2 -enhanced oil recovery (EOR) for liquid-rich unconventional reservoirs has been investigated through core flooding (Wang et al 2017) and field 'huff-n-puff' pilot tests (Hoffman and John 2016). Our literature survey shows that field applications of enhanced oil recovery (EOR) for unconventional oil reservoirs are limited.…”
Section: Introductionmentioning
confidence: 99%